2011
DOI: 10.1902/jop.2011.100664
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Periodontitis in a Sample of Regular and Irregular Compliers Under Maintenance Therapy: A 3‐Year Follow‐Up Study

Abstract: RC patients presented a lower progression of periodontitis and tooth loss compared to EC patients. This result highlighted the influence of the pattern of compliance in maintaining a good periodontal status. Moreover, important risk variables such as smoking and diabetes influenced the periodontal status and should be considered when determining the risk profile and interval time for PMT visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…In another study, 92 percent of patients with an adequate level of health literacy knew that a blood pressure of 160/ 100 mmHg is high, but only 55 percent of patients with an inadequate level of health literacy knew this (18). Periodontal disease is similarly chronic in nature; patient understanding and compliance are essential for successful long-term maintenance and periodontal stability (19,20). The results of this study indicated that race, smoking, and oral health literacy were significantly associated ( P < 0.05) with periodontal health status (health/mild, moderate, severe).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 92 percent of patients with an adequate level of health literacy knew that a blood pressure of 160/ 100 mmHg is high, but only 55 percent of patients with an inadequate level of health literacy knew this (18). Periodontal disease is similarly chronic in nature; patient understanding and compliance are essential for successful long-term maintenance and periodontal stability (19,20). The results of this study indicated that race, smoking, and oral health literacy were significantly associated ( P < 0.05) with periodontal health status (health/mild, moderate, severe).…”
Section: Discussionmentioning
confidence: 99%
“…However, 4 studies Oliveira Costa et al 2011;Costa et al 2014) shared the same subject cohort. Therefore, out of this cohort of studies, the study having the longest follow-up period was selected for data analysis (Costa et al 2014).…”
Section: Study Selectionmentioning
confidence: 99%
“…Not all individuals are equally susceptible . Various biological, environmental and social factors interplay to modify periodontal disease severity and progression …”
Section: Introductionmentioning
confidence: 99%
“…It is well‐established that periodontal treatment without proper SPT is of little value . Compliance with routine SPT is essential, and recurrence of periodontal disease is high among non‐complying individuals . Deterioration in periodontal health occurs also in the inadequately treated patient .…”
Section: Introductionmentioning
confidence: 99%